ROLE OF SPICES IN FOOD FOR IMMUNE BOOSTING - .M, Laksita; Priya.A, Jothi (International Journal of Psychosocial Rehabilitation, 2020)
“Let food be thy medicine and medicine be thy food," as said by the father of medicine, Hippocrates, in 431 B.C. Nature has provided us with a spread of treatment modalities within the sort of food. Only within the past 60 years have we forgotten our medicinal "roots" in favor of patented medicines. While pharmaceutical ingredients have their value, we should always not overlook the well-documented, non-toxic, and inexpensive healing properties of food. Spices are esoteric food adjuncts that have been used as flavoring and coloring agents and as preservatives for thousands of years. Spices have also been recognized to possess medicinal properties, and their use in traditional systems of drugs has been on record for an extended time. With the advancement within the technology of spices and on knowledge of chemistry in immunity and pharmacology of their active principles, their health benefit effects were investigated more thoroughly in recent decades. This review presents the role of various spices in immune-boosting.